Cognitive remediation therapy for partially remitted unipolar depression: A single-blind randomized controlled trial - Listunova, Lena; Kienzle, Johanna; Bartolovic, Marina; Jähn, Anna; Grützner, Thea M.; Wolf, Robert Christian; Aschenbrenner, Steffen; Weisbrod, Matthias; Roesch-Ely, Daniela (Journal of affective disorders, 2020)
Background - There is an urgent need for the development and evaluation of targeted interventions for cognitive impairment (CI) in patients with (partially) remitted major depressive disorder (MDD). The aim of our study was therefore to evaluate the effect of cognitive remediation therapy (CRT) on cognitive and psychosocial functioning in a sample of patients with MDD, taking into account comorbidity, psychopathology, remission status and CI profile. Furthermore, we compared a generalized training (GT) with an individualized training (IT) approach regarding their effects on cognition. - Methods - Sixty-two MDD patients in partial remission with CI were randomly assigned to a control group (CG), IT or GT. Participants of GT trained six cognitive subdomains (divided attention, selective attention, alertness, working memory, planning and response inhibition), whereas participants of IT trained their three most deficient cognitive subdomains as identified at baseline. Participants of both intervention groups trained three times per week over a five-week period. Both training groups received additional 30-minute compensatory-transfer sessions once per week. - Results - Attention appeared to be the most frequently impaired cognitive domain as well as the domain which was significantly improved by CRT, with medium to large effect sizes. No difference in improvement was found between IT and GT. The analyses also revealed greater improvement in self-assessed psychosocial functioning in training participants (GT and IT combined) compared to the CG. - Limitations - Due to the small sample size, the present results are preliminary in nature. - Conclusion - CRT was well accepted, and patients transferred the attentional improvement to real life, as measured by self-assessed psychosocial functioning. IT yielded no additional advantages over GT. We propose CRT as an integral part of the treatment plan for patients with depression suffering from CI.
Gesehen am 09.10.2020